Pelatihan Penggunaan Smart Simulator Elecronic Fuel Injection (EFI) Pada Motor Dalam Meningkatkan Aktifitas Pembelajaran Di SMKN 1 Kotobaru Kab. Darmasraya - Milana, Milana; Hidayat, Nuzul; Sugiarto, Toto; Wagino, Wagino; Purwanto, Wawan (J-CoSE: Journal of Community Service & Empowerment, 2023)
The main aim of SMK is to prepare students to have the practical skills and knowledge needed to enter the world of work. After completing education at vocational school, students can immediately work or choose to continue their education to a higher level. The alignment between the vocational school curriculum and industry demands, especially in graduate skills training (link and match), is currently not yet optimal so it is not adequate to meet the needs of the world of work, industry and business. Even though certain efforts and policies have been made, there are still a number of problems faced by vocational school students. At SMKN 1 Koto Baru, one of the fundamental problems that need special attention in learning is the lack of availability of Electronic Fuel Injection (EFI) competencies. This skill is a very important competency, especially in the Motorcycle Engineering and Business (TBSM) program. The results of observations in schools show that practical equipment for both teachers in the teaching process and for students as practical objects is sufficient and always updated. This happens because SMKN 1 Koto Baru has workshop and laboratory facilities which are equipped with adequate equipment. Apart from that, the instruments used in the practicum are good and can be operated according to the standards they should be. Therefore, training was carried out on the use of the smart simulator to increase learning activities because it involved technology in this training which provided new experiences to students. From the results of the activity, it can be seen that students are very enthusiastic and have increased activity in learning because they can carry out a more complete and clear exploration of learning about the EFI system on motorbikes